2012
DOI: 10.1016/j.jep.2012.09.022
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding of the Mexican sedative and anxiolytic plant Galphimia glauca

Abstract: Ethnopharmacology relevance Galphimiaglauca (Malpighiaceae) is a Mexican plant popularly used as a tranquilizer in the treatment of nervous system disorders, although it is also used to treat other common illnesses. Aim of the study The aim of this investigation is to find out if populations of Galphimiaglauca collected in different regions and ecosystems in Mexico actually belong to the same species by using the contemporary technique of DNA barcodes. Our previous metabolic profiling study demonstrates that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 27 publications
4
25
0
Order By: Relevance
“…For example, to set doses for the cure of ailments using these species, quantitative analyses of the active ingredients for comparison between selected batches must be developed, as reported in previous studies (Cristians et al, 2014 ; Pérez-Vásquez et al, 2014 ). The overall results agreed with the findings of Sharma et al ( 2012 ), one of the few reports that combine molecular analysis based on phylogeny and chemical studies using TLC for the quality control of a Mexican medicinal plant, Galphimia glauca .…”
Section: Discussionsupporting
confidence: 90%
“…For example, to set doses for the cure of ailments using these species, quantitative analyses of the active ingredients for comparison between selected batches must be developed, as reported in previous studies (Cristians et al, 2014 ; Pérez-Vásquez et al, 2014 ). The overall results agreed with the findings of Sharma et al ( 2012 ), one of the few reports that combine molecular analysis based on phylogeny and chemical studies using TLC for the quality control of a Mexican medicinal plant, Galphimia glauca .…”
Section: Discussionsupporting
confidence: 90%
“…A second study utilizing DNA barcoding as a molecular marker confirmed the clear differences among the plant populations used in the former study [ 78 ]. The results found in this study indicated that the plants from all seven populations analyzed do not belong to the one Galphimia glauca species as labeled in the respective herbarium, on the contrary, there could be at least three different species of the genus Galphimia .…”
Section: Taxonomical Misinterpretations In the Galphimiamentioning
confidence: 63%
“…On the specimens used in this study, the assessed DNA barcode regions were successfully amplified using primers designed to evaluate plants (Tokuoka & Tobe, 2006;Chen et al, 2010;Sharma et al, 2012). Most samples were successfully amplified through direct sequencing of the PCR products using the same primer pairs, which generated high-quality bidirectional sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, several species were represented by only one specimen, where it was not possible to evaluate the intraspecific species variation and also not able to concatenate the regions in order to test species discrimination. Sequences of the universal primers for evaluating DNA barcodes, including those for ITS1, ITS2 (ITS1+ITS2, herein named as ITS region) and rpoC1, and general PCR reaction conditions, were obtained from previous studies (Tokuoka & Tobe, 2006;Chen et al, 2010;Sharma, Folch, Cardoso-Taketa, Lorence, & Villarreal, 2012). All PCRs were performed in 25 μL reaction volumes with 12.5 μL of PCR Master Mix (Promega Corp., Madison, Wisconsin), 1.25 μL each of 10 μM primers (upstream and downstream), and 10 μL of diluted (10-to 100-fold) DNA template.…”
Section: Plant Materials and Genetic Analysis Of Dna Barcode Candidatesmentioning
confidence: 99%